TUHAN DALAM PERSPEKTIF FILSAFAT PENDIDIKAN ISLAM - Abdul Matin Bin Salman; Nur Sahed (EL-TARBAWI, 2017)
Islamic education is an effort to introduce a man to his God, to be more aware of the basic potentials and tasks in this world. This study concludes that Islamic education is essentially the source, the basis and the purpose of the God itself. God becomes the focal point of all the development of Islamic education. However, God as a center of Islamic education is often interpreted as a Theocentric belief, which neglects the humanity, so Islamic education only produces humans who are pious in private (hablum min Allah) but weak in social piety. So, there must be a comprehension of anthropocentrism, by which the unity of God has implications for the awareness of human values. This way, Islamic education, in the end, will give birth to humans who are pious privately and socially.Keywords: God, philosophy, Islamic education